(untitled) (AYUSHDHARA, 2020)
Pregnancy is often considered to be the most beautiful phase of a women’s life. It fills her life with a unique happiness and sense of fulfilment. Woman plays a very important role in producing, carrying, bearing foetus in womb, bringing up, maintaining, supporting & nourishment of child. Oedema of pregnancy is termed as Garbhini shotha kind of complication or Upadrava mentioned in Harit samhita & Kashyap samhita. In advancing era of modern Medicine for curative aspect of Antenatal care i.e. aiming at better maternal as well as foetal well being there are still many complication arising in pregnancy. In modern science, numerous efforts have been taken to treat Oedema of pregnancy, but there is only symptomatic treatment along with side effects. Due to high percentage of Garbhopadrava shotha has to keep in mind to find out remedy for it. In Samhitas the brief description of Garbhini shotha and its Chikista is mentioned. It is humble attempt to expand the concept of Garbhini shotha according to Ayurveda to avoid the complications related to the disease.